A Linear Programming Solution to Dynamic Leontief type Models - Wagner, Harvey M. (Management Science, 1957)
Much research has been undertaken in the past several years on the uses of Leontief input-output matrices; applications have been made ranging from industrial growth models to models of interregional dynamics to estimates of structural changes in the economy. This paper discusses a general linear programming formulation of Leontief type relationships. Since we may construct models for a single firm analogous to Leontief macro-economic systems, our results are applicable to a wide variety of situations.